Effect of Niclosamide (Bayluscide WP 70o), Anacardium occidentale Hexane Extract and Euphorbia splendes Latex on Behavoir of Biomphalaria glabrata (say, 1818), under Laboratroy Conditions. - Jurberg, Pedro (1995)
Universidade do Estado do Rio de Janeiro. Instituto de Psicologia. Rio de Janeiro, RJ, Brasil.